2012
DOI: 10.1177/1078155212455939
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to adjuvant endocrine therapy in women with breast cancer

Abstract: The majority of patients who were prescribed adjuvant endocrine therapy for breast cancer at the Cross Cancer Institute remained on therapy for at least 2 years and were adherent. Longer follow-up by Cross Cancer Institute practitioners may help decrease discontinuation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…Women who undergo hormonal therapy need to take tamoxifen or aromatase inhibitor orally, on a daily basis for a total of 5 years. However, epidemiological studies based on different databases and different methodologies concluded that adherence and persistence to adjuvant hormonal therapy among breast cancer survivors is suboptimal [16,17,18,19,20,21,22,23]. For example, in line with our rather long term study results, the French National Health Insurance System database reported a discontinuation rate of 39.5% (95% CI 32.9 -47.0) after 3 years of tamoxifen intake [19].…”
Section: Discussionsupporting
confidence: 72%
“…Women who undergo hormonal therapy need to take tamoxifen or aromatase inhibitor orally, on a daily basis for a total of 5 years. However, epidemiological studies based on different databases and different methodologies concluded that adherence and persistence to adjuvant hormonal therapy among breast cancer survivors is suboptimal [16,17,18,19,20,21,22,23]. For example, in line with our rather long term study results, the French National Health Insurance System database reported a discontinuation rate of 39.5% (95% CI 32.9 -47.0) after 3 years of tamoxifen intake [19].…”
Section: Discussionsupporting
confidence: 72%
“…Women in our study were treated more recently (2005-2010) compared with a timeframe of 2002-2004 in above-cited study [8]. A single-site study performed in 2006 reported similar rates of initiation and persistence [39]. …”
Section: Discussionmentioning
confidence: 92%
“…Current treatment strategies focus on surgery, in combination with radiotherapy and chemotherapy. However, overall survival and mortality rates, in particular for late-stage breast cancer patients, remain poor ( 6 ). A deeper understanding of breast cancer tumorigenesis may aid the development of more effective treatment measures.…”
Section: Introductionmentioning
confidence: 99%